A double-edged sword - Vandebotermet, Martijn (Breathe (Sheff), 2020)
In medicine, not everything is what it seems and sometimes you need all the pieces of the puzzle in order to complete the diagnosis. This is a case of a disease with two different faces and a review of its respiratory impact. https://bit.ly/2SDKwE5